CHARACTERIZATION OF PLANT PATHOGENIC VIRUS CAUSING MOSAIC SYMPTOM ON TOMATO PLANT ( Lycopersicon esculentum MILL.) - Tutung hadiastono (Journal of Tropical Plant Protection, 2012)
A virus obtained from mosaic symptom of leaves of tomato plant (Lycopersicon esculentum Mill.) planted at Dau district, Malang regency, East Java province, was identified as a strain of cucumber mosaic virus. The virus infected plants of 5 species, including 3 species of legumes and 2 species of Solanaceae. It tolerated for 6 hours aging and 1:100 dilution. Broadbean, Dolichos lab-lab, soybean, tomato, and pepper, are useful in distinguishing this virus from others. The last two plant species showed spesific symptoms. There was no symptom observed on soybean and D. lab-lab.Keywords: Cucumber mosaic virus; Lycopersicon esculentum; Symptom